2020
DOI: 10.1093/jxb/eraa244
|View full text |Cite
|
Sign up to set email alerts
|

Variation in zinc concentration of sweetcorn kernels reflects source–sink dynamics influenced by kernel number

Abstract: Grain yield and mineral nutrient concentration in cereal crops are usually inversely correlated, undermining biofortification efforts. Here, sink size, expressed as kernel number per cob, was manipulated by controlling the time when the silks of sweetcorn (Zea mays) cv. Hybrix 5 and var. HiZeax 103146 were exposed to pollen. Twelve other varieties were manually pollinated to achieve the maximum potential kernel number per cob, and kernel Zn concentration was correlated with kernel number and kernel mass. As ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, when the objective is to maximize nutrient production, some compromises are possible. Cheah et al [283] reported that, although there was a negative correlation between the number of kernels per cob and kernel Zn concentration, total kernel Zn accumulated per cob increased with increasing kernel number. Therefore, obtaining high kernel Zn concentrations and high yield in sweet corn is still a challenge.…”
Section: Antioxidants Vitamins and Mineralsmentioning
confidence: 99%
“…Furthermore, when the objective is to maximize nutrient production, some compromises are possible. Cheah et al [283] reported that, although there was a negative correlation between the number of kernels per cob and kernel Zn concentration, total kernel Zn accumulated per cob increased with increasing kernel number. Therefore, obtaining high kernel Zn concentrations and high yield in sweet corn is still a challenge.…”
Section: Antioxidants Vitamins and Mineralsmentioning
confidence: 99%
“…Hybrix 5 and a high zeaxanthin experimental variety var. HZ 103146, chosen due to their differing capacity to accumulate Zn in plant tissues and their different yield potentials (Cheah, O′Hare, Harper, & Bell, 2020; Cheah, O′Hare, Harper, Kochanek, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, the considerably shorter period from pollination to harvest in sweetcorn (21–25 days) compared with maize (>50 days) suggests a narrower window for Zn accumulation and storage in kernels. A previous study also determined that Zn concentration is typically diluted in high‐yielding varieties with many kernels per cob (Cheah, O′Hare, Harper, & Bell, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…P remobilization fluxes were calculated as the percentage of P in different organs to the grain P content. Micronutrient concentrations in the grains were determined (Cheah et al, 2020) and analyzed using inductively coupled plasma (Zasoski and Burau, 1977). Phytic acid (PA) concentration was determined as described by Haug and Lantzsch (1983).…”
Section: Sample Collection and Determinationmentioning
confidence: 99%